Analisis Resepsi Viewers Terhadap Tayangan Mistis Sableng TV - Arli Andianto; Santi Delliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The problem in this research is how the audience's acceptance of the mystical Sableng TV shows based on Stuart Hall's theory of meaning, namely Encoding and Decoding. This study aims to find out how the audience interprets the mystical show from Sableng TV episode "Kuntilanak Dipukul Batako Sampai Terpental Asli". In this study, the approach used is a qualitative approach that focuses on the mystical shows that have sprung up and become one of the content that is watched by many audiences as entertainment and information that is often found on social media such as Youtube and other social media by using the results of interviews. in-depth and documentation of several informants which will later produce three categories of audience positions which are part of Stuart Hall's reception theory, namely Dominant Hegemony, Negotiation and Opposition. So researchers can conclude the results of research on Viewers Reception Analysis on Sableng TV Mystical Impressions